2018
DOI: 10.1177/2058739218772243
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for peritoneal dialysis–associated peritonitis

Abstract: The purpose of this study was to summarize the pathogens that cause peritoneal dialysis (PD)-associated peritonitis and to identify risk factors for PD-associated peritonitis. This retrospective study included 115 end-stage renal disease (ESRD) patients receiving PD therapy. Patients were categorized into two groups: peritonitis group (n = 41) and nonperitonitis group (n = 74). Clinical data and laboratory tests were collected from medical records. The multivariate logistic regression model was used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Many risk factors are known to increase the risk for PD peritonitis, including, but not limited to, low serum albumin, low serum phosphorus, intestinal disorders, and colonic diverticulosis. 1 , 2 The most common pathogens for PD-related peritonitis are coagulase-negative staphylococcal species that commonly colonize human skin and hands and Staphylococcus aureus that together are responsible for 50% or more of infections in most series. 3 , 4 A pittii , a member of the Acinetobacter calcoaceticus - baumannii complex, is a strictly aerobic, gram-negative, nonmotile, nonlactose fermenting, oxidase-negative, catalase-positive coccobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors are known to increase the risk for PD peritonitis, including, but not limited to, low serum albumin, low serum phosphorus, intestinal disorders, and colonic diverticulosis. 1 , 2 The most common pathogens for PD-related peritonitis are coagulase-negative staphylococcal species that commonly colonize human skin and hands and Staphylococcus aureus that together are responsible for 50% or more of infections in most series. 3 , 4 A pittii , a member of the Acinetobacter calcoaceticus - baumannii complex, is a strictly aerobic, gram-negative, nonmotile, nonlactose fermenting, oxidase-negative, catalase-positive coccobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Similarly, both diarrhoea and constipation have been identified as risk factors for PD peritonitis. 34,35 It has been reported that peritonitis can be caused by transmural migration of intestinal microbes during GI upset, potentially facilitated by uraemia-associated gut dysbiosis and enhanced intestinal wall permeability. 34,35 GI symptoms by causing psychological distress, anxiety and depression contribute to fatigue, poor life participation and QOL in patients receiving dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 It has been reported that peritonitis can be caused by transmural migration of intestinal microbes during GI upset, potentially facilitated by uraemia-associated gut dysbiosis and enhanced intestinal wall permeability. 34,35 GI symptoms by causing psychological distress, anxiety and depression contribute to fatigue, poor life participation and QOL in patients receiving dialysis. 19,20,27,28 Considering the high importance of GI outcomes to patients, caregivers and clinicians and their impacts on a range of other critically important outcomes, there is a clear and pressing need to standardise the measurement, monitoring and reporting of GI outcomes in PD trials.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal disorders (i.e., constipation) were also reported to be associated with peritonitis. Wang et al 17 evaluated the risk factors of PD‐associated peritonitis and demonstrated that the presence of gastrointestinal disorder (i.e. constipation) was positively correlated with peritonitis ( r = 1.694, OR = 5.439, p = 0.036). Malnutrition : Hospitalized patients are also susceptible to developing malnutrition due to various factors, 18 including loss of appetite, alteration in taste perception, protein catabolism due to acute illness, and continued protein losses with PD exchanges.…”
Section: Figurementioning
confidence: 99%
“…Wang et al 17 evaluated the risk factors of PD-associated peritonitis and demonstrated that the presence of gastrointestinal disorder (i.e. constipation) was positively correlated with peritonitis (r = 1.694, OR = 5.439, p = 0.036).…”
mentioning
confidence: 99%